Outcomes of pregnancy among unmarried mothers in Malaysia / Norhasmah Mohd Zain - Norhasmah, Mohd Zain (2016)
Births among unmarried women have become a serious concern for public health and reproductive health, especially in developing countries. Such pregnancies are both far more likely to be unintended and to have negative effects on both mother and child. The first objective of this study is to examine the impacts of unmarried pregnancy on pregnancy outcomes among young women in Malaysia. The second is to evaluate the characteristics of unmarried pregnant women and the risk factors of unmarried pregnancy. The final objective is to explore the experiences of women facing unmarried pregnancy. The study employs both quantitative and qualitative data collection procedures, carried out in two phases at six hospitals and six shelters in Peninsular Malaysia. Phase one was a prospective cohort study of pregnant women at four separate times; during their antenatal, shortly after childbirth, one month, and three months after childbirth. Pregnant women with and without marital ties at the point of pregnancy diagnosis were invited to participate in this study. Phase two consisted of in-depth interviews of selected unmarried mothers. A total of 506 women (261 unmarried and 245 married) agreed to participate (92.2% response rate), but 203 unmarried and 200 married women followed up three months after childbirth. Results have shown that most unmarried mothers were adolescents (mean age 19.2 ± 3.9 years) from low socioeconomic groups, who were still studying and living with parent prior to pregnancy. The majority of unmarried mothers were primigravidae, were pregnant due to consensual sexual intercourse and received antenatal care at government health centres. From the multivariate regression analysis, marital status was significantly associated with postpartum depression (OR 3.04; 95% CI 1.29-7.18), preterm birth (OR 1.66; 95% CI 1.05-2.61) and low birth weight (OR 2.79; 95% CI 1.68-4.61). Unmarried mothers were more likely to have poor psychological wellbeing, poor quality of life, lower social support, poor coping strategies and effected job/study and economic condition as compared to married mothers. 43.8% gave their iv child for adoption, while 27.1% chose single motherhood, 17.7% kinship fostering, and 9.9% married the father of the infant. Factors associated with unmarried pregnancy included age (OR 0.64; 95% CI 0.60-0.76), have friends involve with risky behaviour (OR 18.09; 95% CI 4.36-75.14), cigarette used (OR 21.87; 95% CI 2.75-173.93), exposure to pornographic material (OR 10.59; 95% CI 2.49-44.49), sexual health information (OR 10.54; 95% CI 3.32-33.43), contraceptive used (OR 0.17; 95% CI 0.06- 0.51), and social support of significant others (OR 0.79; 95% CI 0.70-0.89). Six themes emerged from the 14 unmarried women who were interviewed in the phase two. Most unmarried women knew the father of their babies and contraceptive use was uncommon among them. There were three primary reactions from women, partners, or families when they knew about the pregnancy; abortion, marriage or staying in shelters. Three choices were made regarding their infant; adoption, motherhood and kinship fostering. Among the impacts faced by women were economic, emotional, health, and physical and social/lifestyle impacts. In conclusion, unmarried pregnancy strongly impacted mental health and birth outcome. It is influenced by various factors which should be addressed by intervention programs. Promoting access to antenatal care and social support programs for unmarried mothers appear important to reduce adverse pregnancy outcomes.